NUMERICAL SIMULATION OF FLAXSEED GUM POTENTIAL IN IMPROVING OIL RECOVERY - Keldibayev, Nurmukhammed (School of Mining and Geosciences, 2023)
The oil and gas industry faces a major obstacle: the requirement to be more eco-friendly and sustainable. To enhance oil production, chemicals are employed, and as a result, there is a demand for environmentally friendly and cost-effective materials. An in-house study in SMG found that flaxseed gum could be used in oil recovery as it increased oil production by 12% in a core flooding experiment. The previous study showed that the method is dominated by gel viscosity and rheology. Thus, this study aims to fill the gap by providing a performance test of flaxseed gum in a simulation using CMG software and to observe the changes in oil recovery factor, cumulative oil recovery, water cut, and residual oil saturation profiles. The study uses the meta-model in CMOST to history match the parameters. Followed by upscaling. The primary outcome obtained from the coreflooding performance evaluation using CMG software revealed that the utilization of Flaxseed gum led to a significant enhancement in the recovery of oil, elevating the recovery rate from 53% to 74.3% and reaching the residual oil saturation of 18.5%. In a field-scale scenario, the implementation of polymer injection decreased the water cut from 95% to 65% and augmented the oil recovery factor by 13% compared to waterflooding. Moreover, the potential for additional oil recovery remains in the field-scale setting since the residual oil saturation has not yet been attained. This research contributes to the exploration of flaxseed gum as a potential solution for EOR applications and provides valuable insights into the mechanism and feasibility of its implementation.
Keywords: Type of access: Restricted; flaxseed gum; EOR; core flood numerical simulation; CMG STARS; CMG CMOST